Development Of Model Based Decoupler For Multi Input Multi Output Distillation Column - Lee, Qiao Hui (2013)
Distillation column is a complex multivariable system and exhibits nonlinear dynamic behaviour due to the complex processing configurations and high product purities. The strong coupling among control loops often invalidates conventional loop controllers. Coupling is a very common phenomenon in multiple input multiple output (MIMO) systems. During processes, multiple control loops are designed for a process plant to control and guarantee the product quality. However, the control loops interact with other significantly. Due to the interaction between the loops, the stability and the product quality of the process may be compromised. Therefore, decoupling control was introduced to reduce the coupling problem in the nonlinear system.